The Role of Edge-Based and Surface-Based Information in Incidental Category Learning: Evidence From Behavior and Event-Related Potentials - Zhou, Xiaoyan; Fu, Qiufang; Rose, Michael (Frontiers in Integrative Neuroscience, 2020)
Although it has been demonstrated that edge-based information is more important than surface-based information in incidental category learning, it remains unclear how the two types of information play different roles in category learning. To address this issue, the present study combined behavioral and ERP techniques in an incidental category learning task in which the categories were defined by either edge-based features or surface-based features. The results from Experiment 1 showed that participants could simultaneously learn both edge-based and surface-based information in incidental category learning, and importantly, there was a larger learning effect for the edge-based category than for the surface-based category. The behavioral results from Experiment 2 replicated those from Experiment 1 and the ERP results further revealed that the stimuli from the edge-based category elicited larger anterior and posterior P2 components than those from the surface-based category, whereas the stimuli from the surface-based category elicited larger anterior N1 and P3 components than those from the edge-based category. Taken together, the results suggest that, although surface-based information might attract more attention during feature detection, edge-based information plays more important roles in evaluating the relevance of information in making a decision in categorization.